A novel cutting machine supports dental students to study the histology of the tooth hard tissue - Zhi-Lan Cheng; Min Cai; Xuan-Yi Chen; Pei Li; Xiao-Hua Chen; Zheng-Mei Lin; Meng Xu (Elsevier, 2019)
Background/purpose: Ground section is the only way to study tooth enamel, and the conventional methods of making ground sections, grinding by hand or using a hard tissue microtome are either too time consuming or money costing. This study aimed to develop and assess a novel cutting machine in making ground sections and learning aid for dental students. Materials and methods: By using the novel cutting machine, the students cut the embedding teeth and got 50 μm ground sections efficiently. A series of fine/coarse combination stones were used for grinding the sections to uniform 20 μm thickness. Self-made ground sections were used in the lab class of tooth tissue. Questionnaires were designed to assess the participants' attitude towards the cutting machine and their knowledge of the tooth tissue before and after making the tooth ground sections. Results: Our findings indicated that the novel cutting machine can act as an efficient tool to make tooth ground sections. Indeed, data indicated that making tooth ground section progress can assist students' understanding of the structure and function of tooth and their pathology knowledge had improved. From a qualitative point of view, the students described making tooth ground section progress improve their practical ability and study interest in oral pathology. Conclusion: Overall, these findings indicate that our novel cutting machine can act as an efficient tool to make tooth ground sections and support dental students to study the pathology of the tooth hard tissue in a simple and functional way.